Contribution of Applying Social Responsibility Practices to Reinforcing Corporate Reputation: A Field Study on a Sample of Clients of Telecommunication Companies Operating in Algeria - Fellague, Mohammed; Sweis, Rateb (Jordan Journal of Business Administration, 2020)
This study aimed to identify the reality of practicing social responsibility in its four dimensions (economic, legal, moral and philanthropic) and its contribution to build company reputation in the cellular communication sector in Algeria, according to the customers’ point of view. The study population included three telecommunication companies’ clients. The sample was restricted to university students and professors estimated at 449 items. The main findings of the study were that: There is a statistically significant impact of applying social responsibility on enhancing corporate reputation, because enterprises can gain and enhance their reputation when they practice and support social activities. Finally, this study sets out some recommendations, the most important of which is: the necessity for companies to direct and intensify their efforts in the area of social responsibility through the establishment of an independent function in the organizational framework to manage social responsibility activities. Also, Algerian companies should pay great attention to adopting a social responsibility strategy in order to build their reputation by gaining the satisfaction and loyalty of customers.